“Truth and Taxes” - McNairn, Jeffrey (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
Part of the roundtable on E. A. Heaman’s Macdonald prize-winning Tax, Order, and Good Government, this essay takes up the book’s claim to offer a social history of knowledge. It explores the central role knowledge production plays in the book to speak to current anxieties in our “post-truth” moment. It suggests that the book can be read as a neo-progressive intervention that refurbishes and updates the progressive historians of the early twentieth century. As a result, this brilliant book twins a rather naturalistic conception of self-interest with a deep commitment to thinking historically about social injustice, power, and the conditions by which truth might replace ignorance.